2019
DOI: 10.4314/as.v18i2.5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of water sources, nutritional qualities and management systems on the prevalence of gastrointestinal helminth infections in ruminants in Benue State, Nigeria

Abstract: Parasitic helminth infections are a frequent burden to livestock farmers. In this study, some domestic ruminants were examined for gastrointestinal helminth infections at some locations in Benue State Nigeria. Six hundred faecal samples were collected per rectum from cattle, goat and sheep in Makurdi, Guma and Gboko. The faeces were analysed using Concentration Method, and direct microscopic examination of helminth parasites. Data were also obtained on the source of drinking water, feeding, and the management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Another study by Tikyaa et al (2019) showed that goats with intensive care had a smaller prevalence of helminth infestation of up to 18,1%, compared to those raised by grazing (38,8%). Tolistiawaty et al (2016) mentioned that ruminants in semi-intensive care have a higher chance infected with helminth worms during grazing.…”
Section: Helminths Eggs In Feces Resultsmentioning
confidence: 96%
“…Another study by Tikyaa et al (2019) showed that goats with intensive care had a smaller prevalence of helminth infestation of up to 18,1%, compared to those raised by grazing (38,8%). Tolistiawaty et al (2016) mentioned that ruminants in semi-intensive care have a higher chance infected with helminth worms during grazing.…”
Section: Helminths Eggs In Feces Resultsmentioning
confidence: 96%
“…Low body condition, heat stress and physical strain when travelling long distances to access feed and water weaken cattle’s immunity (Ayanlade and Ojebisi, 2019 ). Cattle also utilise short grasses and congregate on the few available water sources where the eggs and infective larval stages survive, exposing them to new infections (Tikyaa et al, 2019 ). These conditions increase the incidences and impacts of GIN infestations resulting in increased stress and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Low body condition, heat stress and physical strain when travelling long distances to access feed and water, weakens their immunity (Ayanlade and Ojebisi, 2019). In addition, cattle utilize short grasses and congregate on the few available water sources (Tikyaa et al, 2019) where the eggs and infective larval stages can survive, hence exposing them to new and reinfections. These conditions proliferate the incidences of GIN infestations resulting in increased stress and mortality.…”
Section: Introductionmentioning
confidence: 99%